2006
DOI: 10.1007/s10641-006-9104-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of behaviours and species interactions within home range contours in five Caribbean reef fish species (Family Labridae)

Abstract: Synopsis This study investigated the distribution of behaviours and species interactions within home range contours in five Caribbean labrid species: Halichoeres bivittatus, H. garnoti, H. maculipinna, H. poeyi, and Thalassoma bifasciatum. For this study, contours were defined as: (a) 30%-the core use area, (b) 30-75%-the intermediate activity area, and (c) 75-95%-the peripheral activity area. Behaviours analyzed for this study included: (i) feeding (=biting the substrate or chewing), (ii) chased by pomacentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
2
5
3
Order By: Relevance
“…Thus, the lower densities of damselfishes at Conch Reef may have allowed increased herbivory in restored areas. Territorial damselfishes can also modify the home ranges of numerous species of wrasses (Jones 2007), consistent with the inverse relationship we observed between S. partitus and Thalassoma bifasciatum. Accordingly, damselfishes rapidly colonizing outplanted A. cervicornis may delay or preclude the benefits of coral restoration to fish communities by inhibiting certain fish from using, aggregating, or recruiting to restored areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, the lower densities of damselfishes at Conch Reef may have allowed increased herbivory in restored areas. Territorial damselfishes can also modify the home ranges of numerous species of wrasses (Jones 2007), consistent with the inverse relationship we observed between S. partitus and Thalassoma bifasciatum. Accordingly, damselfishes rapidly colonizing outplanted A. cervicornis may delay or preclude the benefits of coral restoration to fish communities by inhibiting certain fish from using, aggregating, or recruiting to restored areas.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the lower densities of damselfishes at Conch Reef may have allowed increased herbivory in restored areas. Territorial damselfishes can also modify the home ranges of numerous species of wrasses (Jones ), consistent with the inverse relationship we observed between S . partitus and Thalassoma bifasciatum .…”
Section: Discussionsupporting
confidence: 88%
“…Theory indicates that larger fi sh may require larger areas for feeding and that larger fi sh are able to patrol and defend larger areas with less metabolic cost than smaller fi sh are able to do (Kramer and Chapman, 1999). Although such relationships have been observed in some marine fi shes (e.g., Jones, 2007;Taylor et al, 2007;Marshell et al, 2011), others have reported no effect of fi sh size on homerange size (e.g., Lowe et al, 2003;Afonso et al, 2008;Bellquist et al, 2008;Farmer and Ault, 2011; this study). Apparent inconsistencies with theoretical expectations may arise because the relationship between body size and home-range size applies only to comparisons among species or among life stages of a given species (e.g., Jones, 2007).…”
Section: Discussion Home Range Of Black Seas Bass During Inshore Resicontrasting
confidence: 72%
“…Although such relationships have been observed in some marine fi shes (e.g., Jones, 2007;Taylor et al, 2007;Marshell et al, 2011), others have reported no effect of fi sh size on homerange size (e.g., Lowe et al, 2003;Afonso et al, 2008;Bellquist et al, 2008;Farmer and Ault, 2011; this study). Apparent inconsistencies with theoretical expectations may arise because the relationship between body size and home-range size applies only to comparisons among species or among life stages of a given species (e.g., Jones, 2007). For example, juvenile Black Sea Bass displayed restricted use of estuarine habitats in New Jersey, rarely moving more than 120 m (Able and Hales, 1997); this geographic scale of habitat use contrasts markedly with the extent of the area used by adults during their inshore residency (this study) or throughout their life (Moser and Shepherd, 2009).…”
Section: Discussion Home Range Of Black Seas Bass During Inshore Resicontrasting
confidence: 72%
“…While coral reef fishes most commonly collected for the marine aquarium trade (i.e. Pomacentridae) are typically site‐attached with home ranges of a few metres or less (Chapman & Kramer, ; Jones, ), the home ranges of acanthurids have been reported to range from 58 m to 5 km (Claisse et al ., ; Claydon, McCormick, & Jones, ; Green et al ., ; Mazeroll & Montgomery, ). Such home ranges are well in excess of typical home aquaria, with 50% of marine aquarium hobbyists maintaining aquaria with a capacity of less than 400 L (Alencastro, ).…”
Section: The New Era Of Finding Dorymentioning
confidence: 99%